sec A +tanA = CosA/1-sin A
Answers
Answered by
0
Step-by-step explanation:
this may help you. wwwwwwwwwwwwwwwwww
Attachments:
![](https://hi-static.z-dn.net/files/dfb/f15fb2e4cd9e9b8cb1ecfa33b4310b0c.jpg)
Answered by
0
secA + tanA = 1/cosA + sinA/osA
= (1+sinA)/cosA
= {(1+sinA)/cosA}{(1-sinA)/(1-sinA)}
= {(1+sinA)(1-sinA)/cosA*(1-sinA)}
= {(1-sin^2A)/cosA(1-sinA)}
={cos^2A/(cosA(1-sinA))
=cosA/(1-sinA)
The trigonometric fomulas have been used.
Rationalisation has also been used
Similar questions